(untitled) (EU and comparative law issues and challenges series (ECLIC), 2019)
The paper aims to determine situations when arbitrators are personally liable for damages caused and when they enjoy immunity because of their judicial role. There is no uniform approach regarding civil liability of arbitrators. The question is closely connected with the dual nature of arbitration that has a judicial mission despite a contractual origin. Arbitrator’s power derives from a private contract and they receive payment from the parties in exchange for professional services. However, they act as private judges - they resolve disputes which require a binding decision of an impartial third party. Due to the double role of arbitrators, this paper will separately discuss civil liability for breaches of arbitrator’s contractual obligations and breaches of duties regarding their judicial role. Common law countries provide immunity to arbitrators based on equating their function to that of judges. On the other hand, civil law countries emphasize the contractual relationship between the arbitrators and parties and determine liability according to ordinary law of contract. Despite different starting points most jurisdictions accord a certain degree of immunity to arbitrators in the exercise of their judicial role to ensure the finality of arbitral awards and protect the independence and impartiality of arbitrators. Arbitrators are therefore not liable for the procedural or material accuracy of their decisions because in such cases the parties can bring an action against an award. However, almost all legal systems exclude immunity in cases where the arbitrator intentionally violated his judicial duties. The differences between civil and common law countries are greater regarding liability for breaches of the arbitrator’s contractual duties. Contractual limitations and exclusions of liability are also mentioned. The article concludes that absolute exclusions of liability are unenforceable in most jurisdictions. The article will determine which law should apply to the issue of civil liability of international arbitral tribunals. In the absence of legislation and jurisprudence in Slovenia the paper suggests that qualified immunity should apply. Arbitrators should enjoy immunity for judicial acts, except in exceptional cases of fraud and deliberate violations of their judicial duties. For breaches of their contractual duties, arbitrators should be liable according to general rules of contract law.